Collective Intelligence and Selecting the NCAA Men's Basketball Tournaments. (March 2019) - Rogers, Ryan; Strudler, Keith; Baltaxe, David
Every year millions of people fill out brackets, trying to accurately predict the outcome of the NCAA Men's Basketball March Madness tournament. This study examines how collective swarm intelligence might impact these choices in small groups. Rather than working by themselves, groups of people came together to combine their knowledge and opinions and pick brackets collectively. It is generally agreed that collective intelligence is effective in decision-making. However, how and why collective intelligence augments performance has not been totally agreed upon, and the theoretical explanations have been elusive. This study examines groups that are either highly dedicated or high in expertise to see whether they perform differently based on these dimensions.